Answer: 14 gallons of gasoline.
Step-by-step explanation:
given data:
25(x + 3) = 424
where x is the number of gallon of gasoline needed to purchase.
Solution.
25(x + 3) = 424
first we open the bracket
25x + 75 = 424
collect like terms
25x = 424 – 75
25x = 349
divide both sides by 25
25x/25 = 349/25
x = 13.96
x = 14
mathew needs to get 14 gallons of gasoline.
Answer:
1 1/2 x 4 1/2 x 5 = 33 3/4
to get the equation of any straight line we only need two points off of it, hmmm let's use P and Q here and then let's set the equation in standard form, that is
standard form for a linear equation means
• all coefficients must be integers, no fractions
• only the constant on the right-hand-side
• all variables on the left-hand-side, sorted
• "x" must not have a negative coefficient
![(\stackrel{x_1}{6}~,~\stackrel{y_1}{0})\qquad (\stackrel{x_2}{3}~,~\stackrel{y_2}{2}) ~\hfill \stackrel{slope}{m}\implies \cfrac{\stackrel{rise} {\stackrel{y_2}{2}-\stackrel{y1}{0}}}{\underset{run} {\underset{x_2}{3}-\underset{x_1}{6}}}\implies \cfrac{2}{-3}\implies -\cfrac{2}{3} \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-\stackrel{y_1}{0}=\stackrel{m}{-\cfrac{2}{3}}(x-\stackrel{x_1}{6})](https://tex.z-dn.net/?f=%28%5Cstackrel%7Bx_1%7D%7B6%7D~%2C~%5Cstackrel%7By_1%7D%7B0%7D%29%5Cqquad%20%28%5Cstackrel%7Bx_2%7D%7B3%7D~%2C~%5Cstackrel%7By_2%7D%7B2%7D%29%20~%5Chfill%20%5Cstackrel%7Bslope%7D%7Bm%7D%5Cimplies%20%5Ccfrac%7B%5Cstackrel%7Brise%7D%20%7B%5Cstackrel%7By_2%7D%7B2%7D-%5Cstackrel%7By1%7D%7B0%7D%7D%7D%7B%5Cunderset%7Brun%7D%20%7B%5Cunderset%7Bx_2%7D%7B3%7D-%5Cunderset%7Bx_1%7D%7B6%7D%7D%7D%5Cimplies%20%5Ccfrac%7B2%7D%7B-3%7D%5Cimplies%20-%5Ccfrac%7B2%7D%7B3%7D%20%5C%5C%5C%5C%5C%5C%20%5Cbegin%7Barray%7D%7B%7Cc%7Cll%7D%20%5Ccline%7B1-1%7D%20%5Ctextit%7Bpoint-slope%20form%7D%5C%5C%20%5Ccline%7B1-1%7D%20%5C%5C%20y-y_1%3Dm%28x-x_1%29%20%5C%5C%5C%5C%20%5Ccline%7B1-1%7D%20%5Cend%7Barray%7D%5Cimplies%20y-%5Cstackrel%7By_1%7D%7B0%7D%3D%5Cstackrel%7Bm%7D%7B-%5Ccfrac%7B2%7D%7B3%7D%7D%28x-%5Cstackrel%7Bx_1%7D%7B6%7D%29)
![\stackrel{\textit{multiplying both sides by }\stackrel{LCD}{3}}{3(y-0)~~ = ~~3\left( -\cfrac{2}{3}(x-6) \right)}\implies 3y=-2(x-6) \\\\\\ 3y=-2x+12 \implies \stackrel{a}{2} x+\stackrel{b}{3} y=12](https://tex.z-dn.net/?f=%5Cstackrel%7B%5Ctextit%7Bmultiplying%20both%20sides%20by%20%7D%5Cstackrel%7BLCD%7D%7B3%7D%7D%7B3%28y-0%29~~%20%3D%20~~3%5Cleft%28%20-%5Ccfrac%7B2%7D%7B3%7D%28x-6%29%20%5Cright%29%7D%5Cimplies%203y%3D-2%28x-6%29%20%5C%5C%5C%5C%5C%5C%203y%3D-2x%2B12%20%5Cimplies%20%5Cstackrel%7Ba%7D%7B2%7D%20x%2B%5Cstackrel%7Bb%7D%7B3%7D%20y%3D12)
Answer:
B.
Step-by-step explanation:
The negative of a negative is a positive, so B is your choice. Think of it anothe way, if it helps. Imagine that the expression is this:
(-2) + (-1)(-3) since every subtraction problem can be rewritten as an addition problem.
We would first, by orders of operation, multiply the -1 and the -3 getting 3. Then the problem would simplify down to -2 + 3
Just another idea to ponder...
Answer:
Hmm graph 3, i think.
Step-by-step explanation: